Core–shell nanoparticles with tensile strain enable highly efficient electrochemical ethanol oxidation. Issue 27 (2nd July 2021) - Liu, Moxuan; Xie, Miao; Jiang, Yilan; Liu, Zhaojun; Lu, Yiming; Zhang, Shumeng; Zhang, Zhixue; Wang, Xiaoxiao; Liu, Kai; Zhang, Qing; Cheng, Tao; Gao, Chuanbo
Abstract : The tensile strain in an Ag@Pd core–shell nanostructure accelerates the ethanol oxidation reaction (EOR) and improves its selectivity toward complete oxidation of ethanol to CO2 . Abstract : The ethanol oxidation reaction (EOR), the anode reaction of direct ethanol fuel cells, suffers from sluggish oxidation kinetics and low selectivity toward complete oxidation to CO2 . The key to solving the above problems is to design and synthesize high-performance catalysts. In this work, we synthesize Ag@AgPd core–shell nanoparticles that exhibit a significant improvement in catalytic performance. Specifically, in 1.0 M KOH + 1.0 M EtOH, the mass activity of the Ag@AgPd core–shell catalyst reaches up to 12.7 A mgPd −1 with a significantly improved selectivity toward CO2 by 4.5 times compared with commercial Pd/C. This superior performance guarantees that this Ag@AgPd core–shell nanoparticle is among the best-reported catalysts. Mechanism study by density functional theory shows that the tensile strain that originates from the unique core–shell structure decreases the potential determining step by 39%, which plays the most important role in increasing the activity and selectivity. This work demonstrates the effect of the tensile strain in promoting the kinetics and selectivity of the EOR, which may serve as a guide for the design of highly efficient electrocatalysts for general alcohol oxidation reactions by controlled nanoparticle synthesis.